The Role of Extracellular Enzymes Produced by Aspergillus oryzae KKB4 in Biodegradation of Aflatoxin B1 - Sardjono Sardjono; Sri Raharjo; Endang S Rahayu; Kapti Rahayu Kuswanto (Indonesian Food and Nutrition Progress, 2004)
Previous research showed that Aspergillus oryzae KKB4 able to degrade aflatoxin B1 (AFB1) during its growth. According to detoxification test, it was known that extracellular enzymes produced by this mold was able to detoxify AFB1. In this study, the role of these enzymes in biodegradation of AFB1 were further studied. Biodegradation products of AFBI were analyzed using HPLC and the destruction of functional groups were analyzed using IR spectrophotometer. Molecular weight and enzymes activity were also determined. The result showed that extra cellular enzymes of Aspergillus oryzae KKB4 consist of five fractions with molecular weight of 14.2, 20, 23, 29 and 36 kDalton. All enzyme fractions were able to degrade AFB1 with the highest specific activity 3.79 ìg AFBl/mg enzyme protein/20 hrs. The HPLC analysis indicated that biodegradation product of AFB1 was different from untreated AFB1. The infrared spectrum suggest that enzymes degraded lactone ring, cyclo-pentanone reduction and openined difuran ring.